METODE PEMANTAUAN SISTEM PEMBELAJARAN ANAK DI MASA PANDEMIK DI KELOMPOK IKATAN KELUARGA EKA KENCANA MEDAN JOHOR - Andri Ramadhan; Maharani Putri (Jurnal Abdi Ilmu, 2020)
This community service based on the current situation happened, namely an online learning system carried out during the Covid pandemic 19. The goal to be achieved from this service is the emergence of knowledge parents and parents in monitoring the development of a children's education in the future Covid 19 pandemic in the Eka Kencana Family Association Group in Environment XI, Medan Johor District. Low parental understanding of use technology especially communication technology makes them unable to keep an eye on the children. Especially during the Covid 19 pandemic, children were forced to follow education online using a cellphone or laptop. The need for parental supervision is a major factor so that children avoid the negative impacts caused by development technology. The ease of opening sites that have a negative impact on child development, making parental supervision indispensable. Keeping them away from negative things will make them more focused in study. This service is an activity carried out for provide understanding to parents how to monitor the system learning of children using cellphones or laptops during the Covid pandemic 19.